The Influence Of Moral Obligations, Quality Of Tax Services And Business Turnover On Taxpayer Compliance - Putri, Ni Made Tia Aditya; Parwati, Ni Made Suwitri; Mattulada, Andi; Kahar, Abdul (Fakultas Ekonomi Prodi Akuntansi, 2026)
The objective of this research is to investigate the impact of ethical duties, tax administration service excellence, and corporate revenue on the level of tax fulfillment among food service owners within Banggai District.. A numerical methodology integrating an explanatory framework was utilized to scrutinize these interconnected dynamics. The study population comprised 538 restaurants recorded in the Regional Revenue Agency (BAPENDA). Sample size was determined through the Slovin formula, yielding 229 initial respondents, which was subsequently reduced to 216 after excluding 13 outlier data points. Instrument quality was verified through validity and reliability assessments to confirm data accuracy. The analytical procedure involved multiple linear regression alongside t-test-based hypothesis evaluation. Findings reveal that all three independent variables moral obligation, quality of tax services, and business turnover exert a mathematically meaningful and direct upward impact regarding the willingness of dining-place businesses level of compliance and help optimize regional tax revenues in Banggai Regency. Keywords: Moral Obligation, Quality of Tax Services, Business Turnover, Restaurant Taxpayer Compliance.